Infected necrotizing pancreatitis: clinical features, microbial patterns, and outcomes in a Saudi tertiary center - Abulfaraj, Moaz (Frontiers in Cellular and Infection Microbiology, 2025)
Infected necrotizing pancreatitis (INP) is a severe complication of acute pancreatitis (AP) associated with high morbidity and mortality, yet regional data remain limited. We retrospectively reviewed 119 patients admitted with AP to the King Abdulaziz University Hospital, Jeddah, Saudi Arabia, between 2017 and 2025 to characterize risk factors, microbiological profiles, and management strategies. Of these patients, 21 (17.6%) developed INP. Compared with patients with noninfected AP, they were older (mean 60.1 ± 11.2 years, p < 0.05), were more frequently overweight or obese (85.7% ≥ 25 kg/m², p = 0.03), and had higher severity scores (Bedside Index for Severity in Acute Pancreatitis ≥3 in 61.9%, p < 0.01). These baseline differences could explain outcomes rather than infection status. Gallstones (42.9%) and exposure to glucagon-like peptide-1 (GLP-1) receptor agonists (4.8%) were associated with INP. Radiologic imaging confirmed necrosis in all cases, including five abscesses. Of the 21 INP cases, 19 were confirmed by positive cultures from fine-needle aspiration (FNA), drainage, or necrosectomy and 2 by imaging (gas in necrotic collections) plus blood cultures. Microbiological cultures obtained from FNA, drainage, or necrosectomy most commonly identified Escherichia coli (42.9%) and Klebsiella pneumoniae (23.8%), with multidrug resistance detected in one-third of cases. Management strategies included conservative therapy (n = 8), percutaneous drainage (n = 4), endoscopic necrosectomy (n = 5), and surgical necrosectomy (n = 4). Complications included pancreatic fistula, colonic perforation, and sepsis, with an overall mortality rate of 9.5%. Antibiotics were culture-directed in INP but frequently used prophylactically in severe noninfected AP. Early enteral nutrition was implemented in most infected cases. These preliminary findings—limited by a small sample size, single-center design, and a bias toward severe cases—require validation in larger studies; nevertheless, they suggest that older age, obesity, severe presentation, and multidrug-resistant Enterobacteriaceae are defining features of INP in this cohort, and they underscore the importance of antibiotic stewardship and early nutritional support in regional clinical practice.